Introduction to Political Science - Rom, Mark Carl; Hidaka, Masaki; Walker, Rachel Bzostek (OpenStax, Rice University, 2022)
Designed to meet the scope and sequence of your course, Introduction to Political Science provides a strong foundation in global political systems, exploring how and why political realities unfold. Rich with examples of individual and national social action, this text emphasizes students' role in the political sphere and equips them to be active and informed participants in civil society.